2021
DOI: 10.1177/2473974x20988234
|View full text |Cite
|
Sign up to set email alerts
|

Novel Implementation of Virtual Interviews for Otolaryngology Resident Selection: Reflections Relevant to the COVID‐19 Era

Abstract: To address financial and scheduling conflicts associated with residency interviews for otolaryngology candidates, our residency program implemented virtual interviews as an alternative to the traditional in-person format for our visiting subinterns during the 2018-2019 and 2019-2020 interview cycles. Applicants then completed an anonymous survey about their interview experience. We found that, overall, positive attitudes toward virtual interviews increased among 2019-2020 candidates as compared with the year p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…Many different possibilities have been proposed, such as offering virtual interviews to applicants already familiar with the program (i.e., from an away rotation) or who have already completed an intern year at another program. It has also been suggested that programs could offer a round of preliminary interviews virtually before inviting a subset of applicants for in-person interviews to help keep costs down [12]. However, more research is needed on systemic bias in virtual interviewing to mitigate inequalities within the hiring processes prior to making any permanent changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many different possibilities have been proposed, such as offering virtual interviews to applicants already familiar with the program (i.e., from an away rotation) or who have already completed an intern year at another program. It has also been suggested that programs could offer a round of preliminary interviews virtually before inviting a subset of applicants for in-person interviews to help keep costs down [12]. However, more research is needed on systemic bias in virtual interviewing to mitigate inequalities within the hiring processes prior to making any permanent changes.…”
Section: Discussionmentioning
confidence: 99%
“…Some programs recommended decreasing the length of each individual interview due to decreased attention span in a virtual setting [11], however, others warned that longer interviews were needed for applicants to adequately assess the program [12]. After trialing 30-min and 20-min interviews, we ultimately settled on each candidate having three 25-min interviews with a paired faculty member and resident, as well as shorter ''speed dating'' style interviews with the Program Director, Associate Program Director, and Chairperson.…”
Section: Organizing the Interview Daymentioning
confidence: 99%
See 1 more Smart Citation
“…They allow both applicants and the Ph.D. programs to get the most information and find the most qualified applicants ( Al Saiegh et al, 2020 ). As a consequence of the COVID-19 pandemic, recruitment processes have undergone novel changes ( Davis et al, 2021 ; Kenwell et al, 2021 ). Strielkowski (2020) refers to this situation as a digital revolution in academic and higher education centers and believes it to be only one of the consequences of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…A surprising insight was that most applicants preferred traditional on-site interviews and valued them more. Davis et al (2021) addressed the financial and programming issues of implementing VI for Otolaryngology Residency recruitment. Twelve single 15-min VIs were conducted via zoom for 12 applicants who took part in the following online survey to share their experiences and attitudes with the researchers.…”
Section: Introductionmentioning
confidence: 99%